Aplikasi TikTok dan Pola Belajar Generasi Z: Analisis Dampak Media Sosial di Era Digital - Yeni Prestia; Naysilla Azzahra Ramadhani; M Syahrizal Putra (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the influence of the TikTok application on the learning patterns of Generation Z in the digital era through a qualitative descriptive approach using a literature review method. Data were collected from various academic sources, including books and peer-reviewed journals discussing social media, digital behavior, and educational practices among Generation Z. The findings indicate that TikTok significantly shapes learning behaviors by encouraging visual-based, short-duration, and algorithm-driven content consumption. On the positive side, TikTok supports learning motivation, creativity, and access to educational information in an engaging format. However, excessive use of the platform also contributes to decreased concentration, reduced study duration, and the emergence of instant learning habits. These contrasting impacts demonstrate that TikTok functions as a double-edged tool in educational contexts. Therefore, strategic integration of TikTok as an educational medium, accompanied by digital literacy enhancement and guided supervision, is essential to ensure that its use supports effective and sustainable learning outcomes for Generation Z in the digital era.